Evaluation of damage in reinforced concrete columns under biaxial loading - Rodrigues, H. (2013)
The present study is focused on the analysis of damage evolution observed in an experimental campaign on 24 RC columns tested under uniaxial and biaxial loading. The observed damage evolution and damage states are compared for uniaxial and biaxial loading conditions. The test results show that for biaxial loading conditions each damage limit state occurs for lower drift demands when compared with the corresponding test for uniaxial demand (a reduction of 50–75% was found). The deformation demand associated with each damage state is compared with performance objectives proposed in international guidelines. Finally, and based on the philosophy of the Park & Ang uniaxial damage index, two new expressions are proposed for the evaluation of damage in RC elements under biaxial loading. These expressions are calibrated against the experimental results obtained with the tests on columns based on a scoring process to choose the best DI estimator.